Post-Vote Iran: Giving Engagement a Chance - Annalisa Perteghella (Pubblicazioni ISPI, 2017)
2017 is a crucial year for Iran. In January, while the Joint Comprehensive Plan of Action (JCPOA) entered the second year of implementation, in Washington the Trump Administration took office, with the promise to "renegotiate a disastrous deal". In May, in Tehran, the incumbent President Hassan Rouhani won re-election by a wide margin. This Report intends to trace what lies ahead for Iran after the May 2017 Rouhani's re-election. The analysis builds upon the assumption that Iran does not act in a vacuum: the US, as well as the EU actions, will inevitably help define the future trajectory of the country. A trajectory which is set domestically also by the generational transition Tehran is going through. The inter-factional struggle affecting Iran since the early years of the Revolution is now revived by what is actually at stake: the very future of the Islamic Republic.